In vivo antistress and antioxidant effects of fermented and germinated mung bean - Yeap, Swee Keong; Beh, Boon Kee; Mohd Ali, Norlaily; Mohd Yusof, Hamidah; Ho, Wan Yong; Koh, Soo Peng; Mohamed Alitheen, Noorjahan Banu; Long, Kamariah (Hindawi Publishing Corporation, 2014)
Mung bean has been traditionally used to alleviate heat stress. This effect may be contributed by the presence of flavonoids and γ-aminobutyric acid (GABA). On the other hand, fermentation and germination have been practised to enhance the nutritional and antioxidant properties of certain food products. The main focus of current study was to compare the antistress effect of none-process, fermented and germinated mung bean extracts. Acute and chronic restraint stresses were observed to promote the elevation of serum biochemical markers including cholesterol, triglyceride, total protein, liver enzymes, and glucose. Chronic cold restraint stress was observed to increase the adrenal gland weight, brain 5-hydroxytryptamine (5-HT), and malondialdehyde (MDA) level while reducing brain antioxidant enzyme level. However, these parameters were found reverted in mice treated with diazepam, high concentration of fermented mung bean and high concentration of germinated mung bean. Moreover, enhanced level of antioxidant on the chronic stress mice was observed in fermented and germinated mung bean treated groups. In comparison between germinated and fermented mung bean, fermented mung bean always showed better antistress and antioxidant effects throughout this study.